Water Level Monitoring System User Interface for Flood Forecasting - Athira Aina; Faiz Asraf Saparudin (Progress in Engineering Application and Technology, 2024)
Floods are one of the most common natural disasters in Malaysia, occurring nearly every year, particularly during the monsoon season. Floods affected the entire state of Johor in March 2023. The research focuses on three main objectives: designing a user-friendly interface, ensuring reliable data, and developing an effective alert system for critical water levels. Leveraging contemporary technologies like MIT App Inventor, Google Sheets, Apps Script, and ThingSpeak, the system facilitates real-time monitoring and predictive analytics. The study details the systematic integration of these technologies, shedding light on the design process, data integration, and user interface development. Special emphasis is placed on addressing water resource management challenges and flood mitigation through technological innovation, illustrated by project flowcharts, block diagrams, and system flowcharts. Results demonstrate the system’s effectiveness in collecting, processing, and displaying water level data, along with timely alert functionalities. The study’s significance extends to policymakers, engineers, and academics involved in water resource management, offering a foundational framework for deploying monitoring systems in flood-prone areas. The conclusion reflects on project accomplishments and provides future recommendations to advance water level monitoring systems for proactive flood management.